HUBUNGAN ANTARA KECERDASAN SPIRITUAL DENGAN KECEMASAN MENGALAMI CEDERA BERAT PADA PEMAIN BOLA BASKET DI UNIVERSITAS DIPONEGORO SEMARANG - ALVERLY NOVERIANTO; Endang Sri Indrawati (Jurnal EMPATI, 2017)
Anxiety of serious injury are one of the problems athletes had because it makes them feels unconfident and decrease the performance. This study aims to examine the relationship between spiritual intelligence and anxiety of serious injury for basketball player in Diponegoro University Semarang. The population in this study was 155 basketball player that are college student of Diponegoro University and used to played a basketball tournament with university basketball team. 107 basketball player were participated in this study by using convenience sampling. To measure the basketball player’s spiritual intelligence, we used Spiritual Intelligence Scale (24 item, α = .88), to measure the basketball player’s anxiety of serious injury, we used Anxiety of Serious Injury Scale (38 item, α = .92). The result of Spearman’s method showed that there is negative relationship but not significant between spiritual intelligence with anxiety of serious injury toward basketball player in Diponegoro University Semarang, with rxy -.15 and p = .14 (p > .05). The suggestions for next researches are to consider another variable that can affect the anxiety of serious injury, so that the significant result can be expected.